The delineation of intraprostatic boost regions for radiotherapy using multimodality imaging. (November 2016) - Pathmanathan, Angela U; Alexander, Emma J; Huddart, Robert A; Tree, Alison C
Dose escalation to the prostate improves tumor control but at the expense of increased rectal toxicity. Modern imaging can be used to detect the most common site of recurrence, the intraprostatic lesion (IPL), which has led to the concept of focusing dose escalation to the IPL in order to improve the therapeutic ratio. Imaging must be able to detect lesions with adequate sensitivity and specificity to accurately delineate the IPL. This information must be carefully integrated into the radiotherapy planning process to ensure the dose is targeted to the IPL. This review will consider the role and challenges of multiparametric MRI and PET computed tomography in delineating a tumor boost to be delivered by external beam radiotherapy.